A case series of IPOM-AS – intraperitoneal mesh fixation technique for ventral hernia using straight needle suture nylon 2–0 - Arvind K Shukla; Saranshi Shrivastava; Sagar Arora; Avinash Gautam; Jujar Kapadia; Rahul Tayal; Rajesh Maida (Asian Journal of Medical Sciences, 2023)
Intraperitoneal onlay mesh (IPOM) technique of mesh fixation using tackers for ventral hernia is widely done. But using tackers is costly (266.29 USD) and causes early and late post-operative pain. The aim of the study was to choose the better method of surgery for ventral hernia using composite mesh and straight needle suture nylon 2–0 for intraperitoneal mesh fixation (IPOM-AS) and will compare it with conventional IPOM technique in which Fixation of mesh is done by Tacker. Ten patients who were diagnosed with ventral hernia between November 2022 and December 2022 in the Department of Surgery, MGM Medical College and MY Hospital, Indore were taken in our study and IPOM-AS technique was performed using three ports on the left side of the abdomen, after reducing the contents of hernia, the axis for internal attachment of composite mesh is identified and marked with pair of sutures (vicryl and rapid vicryl) and intraperitoneal transabdominal fixation of mesh is done using straight needle suture nylon 2–0 with the help of suture passer. This technique was taken in our study and was assessed for cost-effectiveness, early and late post-operative pain, learning curve, early mobilization, early discharge, early return to work, and long-term complications. All the patients had less early and late post-operative pain according to VAS score (mean VAS score 2 on post-operative 1 and 1 on post-operative 2, no pain during the follow-up period), patients were discharged earlier (mostly on post-operative 1) and early return to work was possible and this technique of intraperitoneal mesh fixation using straight needle suture (2.03 USD) is more cost-effective when we compared these patients with those in whom conventional IPOM was done with the help of a tacker (266.29 USD). Good patient compliance was seen. IPOM using composite mesh and straight needle suture (IPOM-AS) for intraperitoneal mesh fixation in ventral hernia is better accepted by patients than the conventional IPOM using tacker for mesh fixation.